Climate Change in the Underworld: Impacts for Soil-Dwelling Invertebrates - Hiltpold, Ivan; Johnson, Scott N.; Le Bayon, Renée-Claire; Nielsen, Uffe N. (New York: Wiley Online library, 2016)
This chapter reviews and discusses the impact of elevated atmospheric CO2 and climatic changes on three of the functionally most important invertebrate taxa in soil ecosystems: nematodes, insects, and earthworms. The effects of climate and atmospheric CO2 change on soil abiotic conditions vary and numerous biotic feedbacks occur. Many soil‐dwelling insects are herbivores and devastate crops, which impact human societies through yield decreases; therefore an understanding of how climate change will affect their pest status is essential. The chapter discusses potential broader impacts of soil nematode community responses to climate change on ecosystems. Soil‐dwelling insects that feed on roots are usually the juvenile stages of insects that live aboveground as adults. These soil invertebrates can reach astonishing densities, with root‐feeding cicadas of deciduous forests of North America having the largest collective biomass per unit area of any terrestrial animal.